Collective chemo-mechanical oscillations and cluster waves in communicating colloids - Nils Göth; Joachim Dzubiella (Communications Physics)
Abstract Communication and feedback are crucial for the self-organization and the emergent viscoelastic behavior of life-like soft matter systems. However, the specific effects of communication between the individual components on their properties, interactions, and collective dynamics are not fully understood. Here, we report on two-dimensional Brownian dynamics simulations of catalytically active, non-motile hydrogel colloids with explicit resolution of chemical signaling clouds and chemo-mechanical feedback through a size-dependent permeability for the fuel. In particular, we investigate how their spatiotemporal structure and dynamical behavior depend on the communication magnitude and the colloid density. We discover a diverse range of nonequilibrium structures and active phases, including transitions from uncorrelated to synchronized oscillations and the emergence of elastic cluster waves for increasing chemo-mechanical coupling. Our findings highlight microscopic physical principles behind communication-driven cooperativity and could inform the design of active soft matter systems with adaptive functionalities.